Pemanfaatan Ekstrak Daun Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) sebagai Pengawet Tomat - Supriatni, Dina; Said, Irwan; Gonggo, Siang Tandi (Jurnal Akademika Kimia, 2016)
Tomato fruit is one of the fruits susceptible to decay because of its high water content. The durability of tomato can be improved by storing in a humid place or by adding of a preservative. Phaleriamacrocarpa (Scheff.) boerlleaf can act as an antibacterial due to the saponin compounds contained therein. This study aimed to investigate the phaleriamacrocarpa (Scheff.) boerlleaf extract as a preservative for tomatoes, and to determine the concentration of leaf extract to sustain tomatoes texture longer. The method used in this study was the maceration for extraction, and iodometric titration to determine of vitamin C levels before and after curing. The results showed that the pickling tomatoes using phaleriamacrocarpa (Scheff.) boerl leaf extract with a concentration of 6% sustained tomatoes up to 9 days, and the fruit decreased levels of vitamin C from 33.440 mg/100 g material into 27.580 mg/100 g of material.